To assess the effect of intervention package in type 2 diabetes self-care practices, an experimental epidemiological study - Raikar, Kedar J.; Velhal, Gajanan D.; Shukla, Anubha (International Journal Of Community Medicine And Public Health, 2017)
Background: Keeping into mind the importance of diabetic self-care practices for control of diabetes burden and preventable complications, the present study was carried out to introduce appropriate health intervention package which upon operationalization leads to improvement in self-care practices and to assess effect of intervention packages with help of predetermined indicators. The objectives were to study of life style adaptations and self-care practices and to study effects of intervention package. Methods: The present study adapted as an experimental epidemiological study, community based with before and after intervention comparison design. Sample size estimated as 203. Total 250 patients were selected by simple random sampling method and grouped into 8 batches. Intervention package which includes health education, patient counseling, periodic check-up, advise for referral. All batches were followed up with operationalization of intervention package for 12 months. Post intervention data then collected and analyzed with pre intervention data. Results: Effectiveness of intervention package in glycemic control (p<0.046) and decreased calories intake in diabetic patients (p<0.01). Major changes in self-care practices have effect on better glycemic control and calorie intake (p<0.03). Both lifestyle adaptations and self-care practices improved significantly (p<0.01) after intervention. Conclusions: Health and nutritional education, personal counselling, periodic health check-up, Referral advice are important as an intervention package to bring about blood glucose level control, modify diet and lifestyle and to improve self-care practices amongst the diabetic patients.